Detection of genes encoding ompW and ctxA of Vibrio cholerae isolated from shrimp and shellfish at Kedonganan fish market, Bali-Indonesia - Kusuma Praja, Rian Arinta; Sukrama, I Dewa Made; Fatmawati, Ni Nengah Dwi (Oceana Biomedicina Journal, 2019)
Contamination of pathogenic bacteria in food can lead to the emergence of foodborne disease. One of foodborne disease which often occurs in some developing countries such as Africa, Southeast Asia, and Latin America is cholera which is caused by Vibrio cholerae. The disease is transmitted through beverages and food, especially contaminated seafood. V. cholerae has several virulence factors including the outer membrane protein W (ompW) and cholerae toxin (ctx).The ompW acts as a protective barrier and can also be used as a marker specific species of V. cholerae and cholerae toxin is an enterotoxin responsible for the incidence of diarrhea in a cholera outbreak produced by pathogenic V. cholerae. This study was an observational study to determine the level of contamination of V. cholerae by detecting the outer membrane protein W (ompW) and cholerae toxin subunit A (ctxA) gene of V. cholerae in shrimp and shellfish sold at Kedonganan fish market. Samples were taken using total sampling technique and obtained 24 samples consisting of 14 shrimp samples and 10 shellfish samples. Samples were examined using culture methods and biochemical tests, and then further tested using Duplex Polymerase Chain Reaction (dPCR) to detect ompW and ctxA gene. The dPCR assay results showed 8 out of 14 (57.1%) samples from shrimp and 1 out of 10 (10%) samples from the shellfish positive carried ompW gene, and found no positive samples carrying the ctxA gene in samples derived from shrimp and shellfish. Chi square test analysis results indicated contamination of V. cholerae in shrimp was higher than shellfish based on ompW gene (p<0.05). It can be concluded that the shrimp and shellfish at Kedonganan fish market are contaminated by V. cholerae. Further research is needed to detect the virulence factors besides ompW and ctxA of V. cholerae in seafood. Keywords: Foodborne disease, Vibrio cholerae, ompW gene, ctxA gene, and Duplex Polymerase Chain Reaction (dPCR).